2016
DOI: 10.1021/acsphotonics.6b00514
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Moving-Spot Microscopy: Birth and Growth of Laser-Induced Periodic Surface Structures

Abstract: Laser-induced periodic surface structures (LIPSS) are a universal phenomenon observed in all classes of solid materials, giving rise to a variety of self-assembled subwavelength structures with different symmetries. These promising features have opened new opportunities for laser structuring of materials in a wide range of applications, including plasmonics, nanophotonics, nanoelectronics, sensing and even mechanics. However, there is an ongoing debate about the formation mechanism of LIPSS and the current pic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
84
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 115 publications
(90 citation statements)
references
References 39 publications
(92 reference statements)
4
84
1
Order By: Relevance
“…Although SPPs can theoretically only be coupled and propagate at a dielectric/metal interface, laser-induced free-electron generation in semiconductors and dielectrics turns them transiently into a metal-like state, generating conditions for SPP propagation 12 . Yet, there is still a vivid debate about other mechanisms that contribute to the formation of LIPSS in semiconductors, amongst which optical near- and far-field scattering process have recently been identified 14, 15 .
Figure 1Optical micrographs of the Si surface after irradiation with ( a ) N  =  10 and ( b ) N  =  20 horizontally polarized laser pulses at normal incidence ( θ  =  0° ) and F  =  270   mJ / cm 2 .
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although SPPs can theoretically only be coupled and propagate at a dielectric/metal interface, laser-induced free-electron generation in semiconductors and dielectrics turns them transiently into a metal-like state, generating conditions for SPP propagation 12 . Yet, there is still a vivid debate about other mechanisms that contribute to the formation of LIPSS in semiconductors, amongst which optical near- and far-field scattering process have recently been identified 14, 15 .
Figure 1Optical micrographs of the Si surface after irradiation with ( a ) N  =  10 and ( b ) N  =  20 horizontally polarized laser pulses at normal incidence ( θ  =  0° ) and F  =  270   mJ / cm 2 .
…”
Section: Resultsmentioning
confidence: 99%
“…In the present work, we want to focus on a different aspect and illustrate it with new experimental data. We have used the moving-spot modality of fs microscopy 15 , based on recording time-resolved images while the sample is translated using a step size equal to the fringe period. Laser irradiation was performed at θ  =  52° and illumination with a fs probe pulse at θ  =  0° (c.f.…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, during the interaction of silicon with an ultrafast laser in a nonablation regime, the materials melt locally due to the lattice instability induced by a relatively high density of free electrons that exceeds the threshold of nonthermal melting ( n e,thresh ≈ 10 22 cm −3 ) but is below the ablation threshold of silicon . Following the liquid‐phase rapid solidification, crystalline silicon transforms into the amorphous phase . Over above course, femtosecond laser only causes the local phase change of silicon substrate but removes almost no material (Figure S2, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Using nanosecond laser irradiation, Pena et al produced micrometer-sized amorphous humps with a height of a few nanometers 18 . Recently, it has been shown that Laser-Induced Periodic Surface Structures (LIPSS) in form of alternating amorphous and crystalline fringes can be fabricated by scanning the laser beam over the sample surface, employing an adequate choice of spot size, repetition rate and scan velocity 19,20 . In the present work we present a simple strategy to fabricate surface-depressed annular amorphous rings with a central crystalline disk, temporally resolve their formation process, and show how these structures can be scaled and stitched together to form arrays with different symmetries.…”
Section: Textmentioning
confidence: 99%